Sharenting in Malaysia: Balancing Parental Rights and Children’s Privacy in the Digital Age - Jamaluddin, Siti Zaharah; Abu Taher, Mohammad; Ahmad Rujhan, Iman Syamil (Hasanuddin Law Review, 2025)
This study explores the phenomenon of “sharenting,” the widespread practice of parents sharing information, photos, and videos of their children online, within the Malaysian context. As social media becomes deeply embedded in daily life, sharenting serves as a common means for parents to document and share their parenting journey. However, this practice raises significant concerns about striking a balance between parental rights and children’s rights to privacy, consent, and protection from long-term digital exposure. While Malaysian parents often view sharenting as an expression of their rights, it may inadvertently infringe upon the child’s autonomy and digital footprint, which is permanent and difficult to erase. This study examines the existing Malaysian legal framework governing parental and children’s rights, with a focus on the principle of the best interest of the child as the guiding standard. Through a comprehensive review of literature, relevant legislation, and comparative perspective, the study argues that current laws are insufficiently addressing children’s digital privacy and consent rights. It recommends legal reforms that explicitly recognise children’s rights to privacy, consent, and the right to be forgotten, ensuring a more equitable balance between parental authority and the child’s digital autonomy in the digital age.